Pendekatan Psikologi Dalam Studi Islam - Alhadi , Izzah Azizah (STAI Publisistik Thawalib Jakarta, 2023)
The research objective is to describe psychology as an approach to Islamic studies. Qualitative research methods with a library research approach to data collection techniques with documentation studies sourced from journals and books. The results in this study 1) Religious teachings that describe a person's inner attitude, for example,e the nature of faith and piety to Allah, as a pious person who does good and The research objective is to describe psychology as an approach to Islamic studies. Qualitative research methods with a library research approach to data collection techniques with documentation studies sourced from journals and books. The results in this study 1) Religious teachings that describe a person's inner attitude, for example,e the nature of faith and piety to Allah, as a pious person who does good and is honest, all of which are psychological symptoms related to religion. With this psychology,y a person knows the level of religion that is lived, understood,d and practiced besides that as a tool to incorporate religion into one's soul according to their age level. 2) The psychological approach in Islamic Studies is useful for knowing and understanding how the religious level is understood, internalize,d and practiced by a Muslim as well as being able to know the effect of praying, fasting, zakat, hajj and other acts of worship in one's life.